Short Term Functional Outcomes of Arthroscopic Revision ACL Reconstruction - Majed Aswad Jasem AlSaad; Sinan Salah Khudhair Hasan (Open Journal of Physicians and Surgeons, 2025)
Background: the incidence of anterior cruciate ligament reconstruction surgeries is increasing (200,000 ACL reconstruction annually in the United States) with success rate 75-97% and so is the number of revision surgeries for a failed ACL reconstruction also increased. The spectrum of ACL failure includes symptoms of recurrent instability, pain, and/or stiffness. Revision of the arthroscopically Anterior cruciate ligament (ACL) reconstruction failure is treated surgically by ACL reconstruction; this intricate procedure is frequently saved for situations in which the first attempt at ACL restoration has failed. Aim of study: To evaluate the short-term (6 months) functional outcomes of arthroscopic revision ACL reconstruction, using Lysholm knee score. Patient and Methods: the study included 10 young patients with failed ACL reconstruction from October 2022 to November 2023, cases are followed for 6-months. Results: after arthroscopic revision ACL reconstruction, the results showed that the most common score among patients was good knee score rating, which was recorded in 70% (7 of the patients) with Lysholm knee scores ranging from (43-66) pre-operation and (80-89) in Post operation. While other categories included a fair knee score rating, which was recorded in 30% (3 of the patients), with Lysholm knee score 40-50 in pre-operation and 50-70 for post-operation. Conclusion: revision ACL reconstruction led to significant improvements in knee function across various patient characteristics and causes of failure.